Intensive culture of Litopenaeus vannamei without water exchange and with an artificial substrate - Audelo-Naranjo, Juan Manuel; Martínez-Córdova, Luis Rafael; Gómez-Jiménez, Silvia; Voltolina, Domenico (HIDROBIOLÓGICA, 2017)
Aiming to determine the effect of the periphyton growing on artificial substrates, juveniles (3 g initial weight and 440 g m-3 stocking biomass) of the whiteleg shrimp Litopenaeus vannamei (Boone, 1931) , were grown during 32 days in eight 1 m3 cylindrical tanks with 3.7 m2 of total submerged surface. Two culture treatments (with and without artificial substrate or control) were tested with four replicates each. Artificial substrate (Aquamats) provided an additional surface area of 7.2 m2 . The mean dissolved ammonium (NH4 +) and ammonia (NH3) concentrations for the Aquamats group were 39 and 22% lower than the respective values obtained for the control cultures. The artificial substrate stimulated nutrient recycling among the biological components (shrimp, biofilm, bottom microfauna, etc.) since mean shrimp biomass yield was 13% higher for the Aquamats group, and it contained a significantly higher percentage of the total nitrogen and phosphorus inputs than the control treatment. The protein content of shrimp cultured with Aquamats was 21.4% higher than that obtained for the control group, which is explained by the higher availability (and diversity) of the natural food of the periphyton. In view of these results, the use of closed cultures added this artificial substrate seems a viable alternative for shrimp culture.